What are scientific concepts? - Arabatzis, T. (K. McCain and K. Kampourakis (eds.), What is Scientific Knowledge? An Introduction to Contemporary Epistemology of Science, 2019)
In this article I discuss the nature and function of scientific concepts, what it takes to possess them, how they can be represented, and how they can be studied by examining the uses of the scientific terms associated with them. I then examine the epistemological issues that arise when considering conceptual change. Furthermore, I draw a distinction between concepts referring to manifest entities (accessible to observation) and concepts referring to hidden entities (temporarily or permanently unobservable). I argue that the function of scientific concepts is different in the two cases. In the former case, their function is primarily classificatory; whereas in the latter case, their function is primarily explanatory. Finally, I suggest that the epistemological problems generated by the evolution of scientific concepts are more severe in the latter case than in the former.